Investment in children's higher education and household asset allocation in China - Yuanyuan Gu; Mary Arends-Kuenning (Journal of Applied Economics, 2022)
This paper explores how the anticipated expenditure on children's college education affects household asset allocation, applying a two-stage budgeting model of asset demand by using the 2016 China Family Panel Studies Data (CFPS). The empirical results show that if a household plans to send a child to college, the probability of holding risky assets increases by 1.7 percentage points, and the probability of holding investable housing assets increases by 3.8 percentage points. Furthermore, we also find that as the expected year of college entry approaches, households prefer less liquid assets. When the expected year is still far in the future, they prefer liquid assets with high-risk and illiquid assets with high-return. These findings imply that policymakers should make reforms in the financial market and real estate market, as well as provide more kinds of investment products, thereby promoting household investment diversification.
Keywords: 330; children's education investment; China Family Panel Studies; higher education; Household asset allocation; study abroad